RELEVANSI AYAT-AYAT RUQYAH JAMIYAH RUQYAH ASWAJA DENGAN TAFSIR MAFATIHUL GHAIB FAKHRUDDIN AR-RAZI - Abd. Warits; Fathurrosyid (Jurnal Studi Qur'an dan Tafsir, 2023)
Abstract The practice of the ruqyah’s verses often provides stereotypes, unvaforable judgement and claim in the society despite its religious affiliation. One of the stereotypes created paradigm shaped by ruqyah’s tradition as a healing tradition. Even the sentiment of religious institution is a new issue that is ravaging religious as a system of stability in this new modern era. From that causes many religious institutions who elevate their primary objectives not to religion but the interest of pragmatism-politism. In this research, the author will reveal two things that are the subject of ruqyah: First, how the practice of ruqyah is in one of the religious institutions? Second, how the sunni mufasir views the ruqyah’s verses? In this research, the author will use a qualitative approach with analitycal descriptive methods with hypothetical model of library research with the interpretation of mafatihul ghaib as a representative of the sunni mufasir and the Jamiyah Ruqyah aswaja (JRA)’s guide book based on the theory of the qur’an reception, the structural functionalism and ritual perspective Emil Durkhaim. The rest of this research also collected data from various works (books/holly books) and was supported by observation and interviews. The reception of practice in Jamiyah Ruqyah aswaja (JRA) can be implemented into three receptions which are aesthetic, exegent, and fucntional reception. The Verses, there are several passages relevant into the view of the Ar-Razi comparising such as the verses of Syifa’, Al-Alaq, Al-Fatihah, Verses of Qursy, Al-Insyirah, and the scrap of magic. But there are several verses that have no relevance to the view of fakhruddin Ar-Razi wich includes the tortured verses, Verses of arsonist, verses of cataract disease, and verses of cancer cure. Key words: Verses of Ruqyah, Al-Qur’an Reception, Jamiyah Ruqyah Aswaja (JRA) Institution, Structural Functionalism